The Impact of Growth Opportunities, Litigation Risk, Firm Size, and Financial Distress on Accounting Conservatism - Nur Anita Chandra Putry; Mahya Alya Afifah (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2025)
The purpose of this study is to examine the influence of selected factors on accounting conservatism among manufacturing companies listed on the Indonesia Stock Exchange during the period 2018–2023. Data were collected using a documentation method, specifically by obtaining financial statement information from the official websites of both the Indonesia Stock Exchange and the sampled companies. A total of 276 observations were obtained using a purposive sampling technique within a quantitative research framework. The analysis revealed that litigation risk and financial distress had a statistically significant positive effect on accounting conservatism, as indicated by significance values below the 0.05 threshold. In contrast, firm size was found to have a negative influence on the level of accounting conservatism applied. Meanwhile, growth opportunity was not shown to have any statistically significant impact on the extent to which accounting conservatism was implemented by the companies in the sample.